Analisis Tata Kelola Dan Perencanaan Investasi Teknologi Informasi Dengan Metode Cobit Dan Val It - Yayan Hendrian (JURNAL TEKNIK KOMPUTER, 2019)
Abstract  - IT Governance and the development of appropriate information technology, aligned with business strategy and in accordance with the target is a priority, but often development projects are not expected to match the even, there are many information technology development project  failure or canceled  in the middle of the road. That's because information technology governance and IT investment planning are not good. It is necessary to analysis  IT  governenace and  planning of  IT investment. The selected sample is PT. Candi Malindo Bangkit with five (5) respondents involved. Tools in this study using the COBIT  framework  for data  and  opinions about IT governance and Val IT  for  IT  investment  planning. The  selected  domain from the COBIT  framework are  DS4 (continuous service),  DS5 (information system security) and  DS11 (data management), and  the domain of Val IT are Value Governance (VG), Portfolio Management (PM) and Investment Management (IM) . Then based  on  the analysis can be known maturity level of IT governance and IT investment  planning. The analysis shows  that  the current  PT. Candi Malindo Bangkit still at maturity level 1 (one) or at the level of the initial/Adhoc which means IT governance and IT investment planning has been no standardization  process, yet organized  and  implemented  based  on  the  needs  of  a  sudden.Keywords: Audit, IT  Governance,  COBIT,  Val IT